L’illustration marginale d’un ouvrage profane : étude du manuscrit Paris, Bibliothèque nationale de France, français 95, xiiie siècle (1290) - Irène Fabry-Tehranchi (Bulletin du Centre d’Études Médiévales d’Auxerre)
BnF fr. 95 is a late 13th century manuscript containing Arthurian romances and other fictional and didactic texts. The Estoire del saint Graal and Merlin section is the most highly illuminated, with a rich marginal iconography, an unusual feature in the illustration of lay works and in these texts’ manuscript tradition. This article shows how in Merlin and its Vulgate Sequel marginal scenes overlap with widespread subjects in courtly and chivalric vernacular romances, in contrast with Latin and religious works. The reuse of similar patterns in principal and marginal miniatures, examined in the episode of the Battle of Danablaise, where King Arthur fights the Saxon King Rion, highlights the need for a comprehensive reading of text and images, taking into account the mise en page and the different levels of illustration in the manuscript.